Risk Management Strategy in Maintaining Financial Sustainability: A Reflection on the Withdrawal of Muhammadiyah Funds from Bank Syariah Indonesia - Irpan; A. Ifayani Hanurat; Andi Mappatompo (IECON: International Economics and Business Conference, 2025)
This study examines the risk management strategies implemented by Bank Syariah Indonesia (BSI) following the institutional fund withdrawal by Muhammadiyah in 2024. This event raised critical questions regarding BSI’s ability to maintain financial stability and uphold public trust amidst reputational risk. Employing a qualitative case study approach, the research is based on in-depth interviews with BSI management, analysis of financial reports (2023–2024), and regulatory publications. The findings reveal that BSI adopted a three- layered risk management approach—preventive, mitigative, and corrective—to stabilize liquidity, mitigate reputational impact, and strengthen stakeholder confidence. Preventive strategies included diversification of funding sources, enhancement of digital banking infrastructure, and improvement of the CASA ratio. Mitigative measures involved real-time communication, increased fee-based income, and CSR programs grounded in ESG principles. Corrective strategies comprised strengthening internal audits and evaluating systemic resilience. This study offers practical insights for Islamic banking institutions in managing socio-religious financial shocks while upholding Sharia principles and sustainability objectives.